Peroxiredoxin 2 Is a Potential Objective Indicator for Severity and the Clinical Status of Subarachnoid Hemorrhage Patients. (6th February 2023) - Peng, Zheng; Pang, Cong; Li, Xiao-Jian; Zhang, Hua-Sheng; Zhang, Jia-Tong; Zhu, Qi; Xu, Hua-Jie; Gao, Yong-Yue; Zhuang, Zong; Li, Wei; Zhang, Qing-Rong; Lu, Yue; et al.
Abstract : Purpose . We have demonstrated that peroxiredoxin 2 (Prx2) released from lytic erythrocytes and damaged neurons into the subarachnoid space could activate microglia and then result in neuronal apoptosis. In this study, we tested the possibility of using Prx2 as an objective indicator for severity of the subarachnoid hemorrhage (SAH) and the clinical status of the patient. Materials and Methods . SAH patients were prospectively enrolled and followed up for 3 months. Cerebrospinal fluid (CSF) and blood samples were collected 0-3 and 5-7 days after SAH onset. The levels of Prx2 in the CSF and the blood were measured by an enzyme-linked immunosorbent assay (ELISA). We used Spearman's rank coefficient to assess the correlation between Prx2 and the clinical scores. Receiver operating characteristic (ROC) curves were used for Prx2 levels to predict the outcome of SAH by calculating the area under the curve (AUC). Unpaired Student's t -test was used to analyze the differences in continuous variables across cohorts. Results. Prx2 levels in the CSF increased after onset while those in the blood decreased. Existing data showed that Prx2 levels within 3 days in the CSF after SAH were positively correlated with the Hunt-Hess score (R = 0.761, P < 0.001 ). Patients with CVS had higher levels of Prx2 in their CSF within 5-7 days after onset. Prx2 levels in the CSF within 5-7 days can be used as a predictor of prognosis. The ratio of Prx2 in the CSF and the blood within 3 days of onset was positively correlated with the Hunt-Hess score and negatively correlated with Glasgow Outcome Scale (GOS; R = ‐ 0.605, P < 0.05 ). Conclusion. We found that the levels of Prx2 in the CSF and the ratio of Prx2 in the CSF and the blood within 3 days of onset can be used as a biomarker to detect the severity of the disease and the clinical status of the patient.